Memory, identity, and nationalism in European regions - Apryshchenko, V. IU; Karnaukhova, Oxana (IGI Global, 2019)
"This book sheds light on the evolution of memory, identity, and nationalism of countries in the European region. It also explores the urgency of memory and nationalism during periods of crisis and/or austerity measures in contemporary Europe"--
Description based on title screen (IGI Global, viewed 04/06/2019)
Keywords: Europäische Union; Collective memory / Europe; Nationalism / Europe; Group identity / Europe; Kollektives Gedächtnis; Geschichtsbewusstsein; Nationalismus; Osteuropa; Aufsatzsammlung